The Socio-Political Factor in the Christian-Muslim Conflict in Nigeria - Opeloye, Muhib O. (2014)
This study identifies ethno-political factors as the major contributor to the Christian-Muslim conflict in Nigeria, while indicating the secondary role of socio-economic considerations and religious fundamentalism, as exemplijied in the Zangon Karaf riot of 1992 and the Tafawa Balewa and Bauchi disturbances of 1991 and 1995 respectively. The study reveals that the tension that erupted from these episodes merely ignited the bomb of ethno-political rivalry between the minority and majority ethnic groups. The eruption of violence on each occasion was the manifestation of the collective anger of minorities that had been incubating over a long period against the domination of the Hausa-Fulani hegemony. Religious and socio-economic considerations were only incidental factors. It is stressed that, even though the disturbances started as ethnic conflicts, they spread rapidly to other towns in the wake of rumours of their religious connotations. The Christian-Muslim conflict, which is traced back to the 1979 Shari'a controversy, is believed to have done serious damage to the unity of Nigerian society. The article sees the practical solution to this problem as lying more in the use of the school system in inculcating the spirit of mutual acceptance and harmonious co-existence, than in the creation of chiefdoms which tend to cause separation and division.